Maintenance of the Maritime Language Lexicon Through the Learning of the Indonesian Language - Aris Badara (Journal of Language Education and Educational Technology (JLEET), 2019)
The research findings show that the percentage of Bajo language survival in the Abeli Coast reaches 48.75%. This shows that the Bajo language vocabulary on the Abeli Coast has approached extinction. The factors that affect the vocabulary are not preserved are: (a) depreciation and loss of referents related to maritime vocabulary, and (b) domination of Indonesian and Bugis languages against Bajo in the Abeli coast. As one of these anticipations, the results of this study can be implemented in learning Indonesian, especially in class VII, semester 2 of Basic Competence 4.2 Keywords: Maritime ecolexicon; Bajo language; Abeli Coast; Indonesian language learning